Determinants of profitability in the economy of the Republic of Cyprus based on a classical Marxist approach - Kosmas, Petros C.; Ioakimoglou, Elias (My University, 2024)
This paper was designed to explore the factors influencing profitability within the business sector using a methodological framework rooted in Marx’s concept of the profit rate. By addressing the complexities of profitability changes, this study investigated the factors that drive profitability within the business sector of the Republic of Cyprus for the years 2006–2022, including: a period of severe structural crisis and change (2013–2014), a period of recovery (2015–2022) based on the outcomes of the crisis, and a period (2006–2012) against which shifts can be contrasted. The findings of this empirical study suggest that a substantial portion of the increase in profitability since 2015 is due to the reduction in the value of the labour power during the crisis years (2013–2014) and following the COVID-19 pandemic period (2021–2022).
Keywords: Profit rate; Labour productivity; Capital productivity; Wages; Republic of Cyprus